The Road of ERP Success: A Framework Model for Successful ERP Implementation - Candra, Sevenpri (Binus Business Review, 2011)
To compete with nowadays business is to implement technology and align it into their business strategy. One of technology that commonly implement is Enterprise Resource Planning (ERP). This research will examined what are critical success factor of ERP and the impact of their business outcomes. A framework model for ERP Implementation success is constructs from several research or previous study in Implementation ERP. This study will extends in the research field of successful implementation ERP and implication factor for business practice to have more knowledge in term of implementation ERP and their business strategy.Â